Update on the COVID‐19‐associated inflammatory syndrome in children and adolescents; paediatric inflammatory multisystem syndrome‐temporally associated with SARS‐CoV‐2. (31st July 2020) - Singh‐Grewal, Davinder; Lucas, Ryan; Macartney, Kristine; Cheng, Allen C; Wood, Nicholas; Ostring, Genevieve; Britton, Philip; Crawford, Nigel; Burgner, David
Abstract : We provide an update on the state of play with regards a newly described inflammatory condition which has arisen during the current SARS‐CoV‐2 pandemic. The condition has been named paediatric inflammatory multisystem syndrome temporally associated with SARS‐CoV‐2 or multisystem inflammatory syndrome in children. This condition has shown significant similarities to Kawasaki disease and toxic shock syndrome.